Unusual wooden foreign body in the palate - Soubhia, Ana Maria Pires [UNESP]; Ribeiro, A. C P [UNESP]; Martins, L. D.; Silva, A. R S; Lopes, M. A. (Springer Nature, 2007)
We report a case of a palatal calcified foreign body simulating an odontogenic lesion. Surgical exploration revealed a calcified mass that was analysed under light microscopy and identified as a vegetal foreign body. Further scanning electron microscopy analysis revealed that the foreign body was a piece of wood. Hard palate foreign bodies have been reported previously, however, it seems that this is the first case of its kind. © 2007 Nature Publishing Group.
Keywords: case report; dental device; differential diagnosis; foreign body; hard palate; human; jaw tumor; male; middle aged; odontogenic tumor; scanning electron microscopy; wood; Dental Devices, Home Care; Diagnosis, Differential; Foreign Bodies; Humans; Male; Microscopy, Electron, Scanning; Middle Aged; Odontogenic Tumors; Palatal Neoplasms; Palate, Hard; Wood